Temporal Lobe Epilepsy with Amygdala Enlargement: A Morphologic and Functional Study. Issue 1 (3rd February 2012) - Takaya, Shigetoshi; Ikeda, Akio; Mitsueda‐Ono, Takahiro; Matsumoto, Riki; Inouchi, Morito; Namiki, Chihiro; Oishi, Naoya; Mikuni, Nobuhiro; Ishizu, Koichi; Takahashi, Ryosuke; Fukuyama, Hidenao
ABSTRACT BACKGROUND AND PURPOSE Temporal lobe epilepsy (TLE) with nontumoral amygdala enlargement (AE) has been reported to be a possible subtype of TLE without hippocampal sclerosis (HS). The purpose of this study was to clarify morphologic and functional characteristics of TLE with AE (TLE + AE). METHODS We evaluated gray matter volume and cerebral glucose hypometabolism using magnetic resonance imaging (MRI) voxel‐based morphometry (VBM) and voxel‐based statistical analysis of [18F]‐fluorodeoxyglucose positron emission tomography (FDG‐PET) images in 9 patients with TLE + AE as compared with controls. For VBM analysis, we recruited 30 age‐ and sex‐matched healthy volunteers as controls. For the comparison of FDG‐PET analysis, 9 patients with definite mesial TLE with HS (MTLE + HS), and 16 age‐ and sex‐matched healthy controls were recruited. RESULTS In patients with TLE + AE, a significant increase in gray matter volume was found only in the affected amygdala, and no significant decrease in gray matter volume was detected. In addition, significant glucose hypometabolism was observed in the affected amygdala, whereas significant glucose hypometabolism in the hippocampus, a prominent feature of definite MTLE+HS, was not observed. CONCLUSIONS TLE + AE is different from MTLE + HS from morphologic and functional points of view, and the enlarged amygdala per se is potentially an epileptic focus in patients with partial epilepsy.